Lack of vigilance is the main factor of late diagnosis of glycogen storage disease type II in the Republic of Kazakhstan - L. A. Kuzina; G. S. Kaishibayeva (Нервно-мышечные болезни)
Pompe disease is a hereditary autosomal recessive disease characterized by accumulation of glycogen due to decreased activity of acid α-glucosidase enzyme in lysosomes. The disease can develop at any age. Cases with onset after the 1st year of life are attributed to late-onset Pompe disease (LOPD). LOPD has a very wide age range when clinical manifestations appear which significantly complicates diagnosis in adults. A case of verified Pompe disease in the Republic of Kazakhstan is presented. A chronology of clinical manifestations and symptoms, results of paraclinical examinations helping to suspect LOPD and verify the diagnosis by decreased activity of acid α-glucosidase in dry blood spot are described.